Prokrastinasi Akademik Ditinjau dari Kecerdasan Adversitas dan Kontrol Diri - Vera Agustina Yanti; Devy Sofyanty; Danny Ong; Suwantica Suwantica (Neolectura, 2022)
Academic procrastination is the behavior of delaying doing or completing academic tasks, reviewing academic procrastination is important to minimize academic procrastination behavior that will affect student learning achievement. This study aims to empirically determine the influence of intelligence and partial and stimultan self-control on academic procrastination. This research was conducted at University X in Jakarta, the research method uses quantitative methods with purposive sampling techniques. Data collection techniques through questionnaires and interviews with a population of 130 respondents, 56 men and 74 women. Data analysis uses multiple linear regression. Based on the results of the analysis, the following findings were obtained: (1) jointly or simultaneously adversity intelligence and self-control affect academic procrastination, (2) partially adverse intelligence has a negative and significant effect on academic procrastination, (3) partially self-control has a negative and significant effect on academic procrastination.